Self-Confidence Reviewed from the Coach-Athlete Relationship: A Case Study at the Gerak Raga Buana (Gerana) Pencak Silat Academy - Kiki Alghifari Azfa Priatna; Yati Ruhyati; Unun Umaran (Universitas Negeri Semarang, 2026)
In the context of competitive sports training, the psychological aspects of athletes are one of the important factors that determine the success of training and performance during competition. One of these psychological aspects is self-confidence, which is believed to be inseparable from the quality of the relationship between the coach and the athlete during the training process. Based on this, this study aims to determine the effect of the coach-athlete relationship on the self-confidence of pencak silat athletes. This study uses a quantitative method with a correlational approach. The research subjects consisted of 53 pencak silat athletes who were used as respondents. The research instruments used included the Coach–Athlete Relationship Questionnaire (CART-Q) to measure the coach–athlete relationship and the Athletic Self-Confidence Questionnaire (ASQ) to measure the athletes' level of self-confidence. The data obtained were then analyzed using normality tests, linearity tests, Pearson's correlation tests, and simple linear regression tests. The results of the analysis showed a positive and significant relationship between the coach-athlete relationship and athlete self-confidence, although the level of the relationship found was relatively weak. In line with these findings, the regression test results showed that the coach-athlete relationship had a positive effect on athlete self-confidence, but the contribution of this effect was relatively small. This indicates that athletes' self-confidence is not only influenced by their relationship with their coaches, but also by other factors outside the research variables. Nevertheless, these findings confirm that the coach-athlete relationship still plays an important role as a supporting factor in building the self-confidence of pencak silat athletes.